A study on the Jesuits' apothecary shops and medical recipes in the Portuguese Empire (Seventeenth and Eighteenth centuries) - Carvaiho Viotti, Ana Carolina de [UNESP] (Univ Do Vale Do Rio Dos Sinos, 2019)
In addition to the evangelizing and missionary activities, the Society of Jesus was prominent in the establishment of apothecaries and santas casas in places where specialized doctors and apothecaries were not found. In the reductions of Paraguay and Brazil, and in even more distant parts, such as Macao and Goa, these religious took on the task of caring for the inhabitants' bodies, developing, manufacturing, applying, distributing and marketing all sorts of medicines. Between the 16th and 18th centuries, there is a series of works which registered their experiences and indications for the manipulation and application of these remedies, true collections of recipes that combined the knowledge of the most outstanding physicians of those times with preparations made in their pharmacies, often with local ingredients. This research, developed as a post-doctoral project, aims to shed light on four collections of recipes produced, probably by Portuguese Jesuits, between the 17th and 18th centuries, books that are still manuscripts and that give clues about the wide network of information and knowledge produced and transmitted among the Ignatians. The proposal seeks to examine the Jesuits' performance in the preparation, elaboration and dissemination of medicines, considering the organization of works, the use of non-religious and local knowledge and the diseases there mentioned and medicated.
Keywords: medicine; Jesuits; collection of recipes; colonial Brazil; Portuguese Empire